2019
DOI: 10.1002/acr.23604
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Regular Physical Activity After Total Knee or Hip Arthroplasty for Osteoarthritis: Prevalence, Associated Factors, and Type

Abstract: Participation rates increase post-surgery when recovery is stable, but approximately one-third of arthroplasty recipients do not engage in PA at least once per week. As participation is associated with habitual activity pre-surgery, a potential role for behaviour change interventions is suggested. That non-ambulatory activities increase indicates current devices measuring ambulatory activity alone are inadequate for capturing PA. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
(114 reference statements)
0
12
0
Order By: Relevance
“…In the mental component, those < 55 years had the lowest scores postoperatively Older better Townsend [ 29 ] J Knee Surg 2018 356 < 50, 50–59, 60–69, 70–79, > 79 Postoperative WOMAC and overall, pain, and function OKS significantly differed among the age groups ( P < 0.05), with patients younger than 60 years reporting the worst scores in the postoperative time period. Older patients reported better preoperative overall, pain, and function scores and greater post-TKA outcomes than younger patients Merle-Vincent [ 54 ] Joint Bone Spine 2011 264 ≤ 70, > 70, Age older than 70 years at surgery was associated with a higher satisfaction rate (odds ratio of age ≥ 70 years is 3.9 [1.1–14.3]; P = 0.038) Younger better Murphy [ 14 ] Bone Joint J 2018 2838 < 80, ≥ 80 SF-12 PCS, coefficient of ≥ 80-group is − 4.46 (− 6.18, − 2.73), P < 0.001 KJ Oh [ 26 ] Aging Clin Exp Res 2018 79 65–70, ≥ 80 The octogenarian patient group had significantly inferior outcomes for WOMAC and SF-36 score compared to the sexagenarian patient group ( P = 0.009 and P = 0.022, respectively) Naylor [ 28 ] Arthritis Care Res 2018 1289 Post operation 3 years: younger age ( P = 0.0018) was significantly associated with regular physical activity Razak [ 36 ] J Bone Joint Surg Am 2016 3062 Younger age KSS predicted a good outcome at 5 years (OKS: OR of age is 2.66 (2.61–2.71), SF-36 PCS: OR of age is 2.64 (2.59–2.67)) Singh [ 57 ] Osteoarthr Cartil 2010 7139 61–70, 71–80, > 80 Significantly predictors of overall moderate–severe activity limitation 2-years post-TKA was age 71–80 (OR: 2.1 [1.5, 2.8]) and age > 80 (OR: 4.1 [2.7, 6.1]) vs, age ≤ 60 years, and 5 years post-TKA was age 71–80 (OR: 2.4 [1.7, 3.5]) and age > 80 (OR: 4.7 [2.8,...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the mental component, those < 55 years had the lowest scores postoperatively Older better Townsend [ 29 ] J Knee Surg 2018 356 < 50, 50–59, 60–69, 70–79, > 79 Postoperative WOMAC and overall, pain, and function OKS significantly differed among the age groups ( P < 0.05), with patients younger than 60 years reporting the worst scores in the postoperative time period. Older patients reported better preoperative overall, pain, and function scores and greater post-TKA outcomes than younger patients Merle-Vincent [ 54 ] Joint Bone Spine 2011 264 ≤ 70, > 70, Age older than 70 years at surgery was associated with a higher satisfaction rate (odds ratio of age ≥ 70 years is 3.9 [1.1–14.3]; P = 0.038) Younger better Murphy [ 14 ] Bone Joint J 2018 2838 < 80, ≥ 80 SF-12 PCS, coefficient of ≥ 80-group is − 4.46 (− 6.18, − 2.73), P < 0.001 KJ Oh [ 26 ] Aging Clin Exp Res 2018 79 65–70, ≥ 80 The octogenarian patient group had significantly inferior outcomes for WOMAC and SF-36 score compared to the sexagenarian patient group ( P = 0.009 and P = 0.022, respectively) Naylor [ 28 ] Arthritis Care Res 2018 1289 Post operation 3 years: younger age ( P = 0.0018) was significantly associated with regular physical activity Razak [ 36 ] J Bone Joint Surg Am 2016 3062 Younger age KSS predicted a good outcome at 5 years (OKS: OR of age is 2.66 (2.61–2.71), SF-36 PCS: OR of age is 2.64 (2.59–2.67)) Singh [ 57 ] Osteoarthr Cartil 2010 7139 61–70, 71–80, > 80 Significantly predictors of overall moderate–severe activity limitation 2-years post-TKA was age 71–80 (OR: 2.1 [1.5, 2.8]) and age > 80 (OR: 4.1 [2.7, 6.1]) vs, age ≤ 60 years, and 5 years post-TKA was age 71–80 (OR: 2.4 [1.7, 3.5]) and age > 80 (OR: 4.7 [2.8,...…”
Section: Resultsmentioning
confidence: 99%
“…Among the nine studies in which PROM differed according to age, two studies reported that better PROMs were achieved after TKA in older patients [ 29 , 54 ] and five studies reported that younger patients had better PROM after TKA [ 26 , 28 , 36 , 57 , 60 ]. However, the baseline age of the patients was 80 years in two of the studies, and in one study the patients’ limitation of activity increased fourfold over the age of 80 years, and it was difficult to compare the differences in PROM in patients age < 80 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in patients with knee and hip arthroplasty, preoperative regular participation in physical activity also was the strongest predictor of physical activity 3 years postoperatively. 19 A possible explanation is patient motivation, which is undoubtedly high in cases of continued sports participation despite debilitating knee OA. Likewise, high patient motivation was associated with improved postoperative activity levels in 139 French HTO patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a patient can shift from his enduring calm and cooperative nature into a temporary anxious and negative personality affecting his coping strategies resulting in a wait and see attitude. Naylor et al [69] reported an association between the habitual activity pre-surgery and the post-surgery participation in physical activity, where patients tend to stick to their habitual physical activity patterns; whereby, approximately one-third of the patients did not engage in physical activity at least once a week after 1-3 years after THA surgery.…”
Section: Implications For Future Researchmentioning
confidence: 99%